Weight reduction via life-style modifications results in reverse remodelling and cardiac functional improvement in a patient with obesity. Issue 3 (May 2017) - Hou, Chang; Zheng, Bo; Yang, Ying; Wang, Xin-Gang; Zhang, Bin; Shi, Qiu-Ping; Chen, Ming
Summary: The prevalence of obesity has increased strikingly in recent years. Obesity is associated with increased left ventricular end-diastolic dimension (LVEDD), ventricular wall thickness, left ventricular (LV) mass, left atrial diameter, subtle myocardial systolic as well as diastolic dysfunction and has been identified as an independent predictor of these changes. It's convinced that weight reduction results in cardiac reverse remodelling, while the functional changes after weight reduction are variable. Here, we present a recent case of man with moderate obesity who acquires favourable regression in chamber size, wall thickness and significant improvement in cardiac function. Briefly, after life-style modifications and comprehensive secondary prevention, great amounts of weight loss was achieved simultaneously with decreased LVEDD and increased LV ejection fraction. As dietary intervention and regular physical activity are pivotal for these benefits, this non-invasive approach for weight loss should be advocated in selected patients.